Exploring EFL Students’ Problems in Listening Comprehension: Menjelajahi Masalah Siswa EFL dalam Pemahaman Mendengarkan - Sari, Nurhidayah; Fithriyana, Rinda (Universitas Muhammadiyah Sidoarjo, 2019)
Listening is a challenging sll for my EFL learners. They seem to do the assignment without showing good comprehension on their answers. This research aims to find out the students’ problems in listening comprehension and identify the factors contributing to the problems. The second semester students in academic year 2017/2018 are the subject of the research. The data were collected by using observation, interview and documentation. The results of the research showed that the students still have low listening comprehension. The most difficult indicator of listening comprehension is making inference. There are only 28% students can answer the questions related making inference. The students also have low confidence in listening skill. They cannot concentrate well in listening to the spoken texts. Those problems are influenced by two factors, internal and external factors. Understanding students' problems leads to the idea of providing better strategies and materials in learning activities.